JQuery 1.4 animation techniques beginner's guide : quickly master all of jQuery's animation methods and build a toolkit of ready-to-use animations using jQuery 1.4 /: quickly master all of jQuery's animation methods and build a toolkit of ready-to-use animations using jQuery 1.4. (2011) - Unknown
No abstract available